New Vespertilio murinus (Chiroptera) Winter Records. An Indication of Expansion of the Species’ Winter Range? - Godlevska, L.V. (Вестник зоологии, 2013)
Absence of winter records, known long distance movements of parti-coloured bats ringed in North-eastern (NE) Europe, and some observations of seasonal concentrations of migrating animals had enabled to consider Vespertilio murinus, until quite recently, as a migratory species wintering outside Ukraine and NE Europe as a whole. During the last years the species had been found in the winter season (November — middle March) in Ukraine in 14 provinces and in the AR Crimea: contact records in 7 provinces, observations of autumn display song in 9 provinces and in the AR Crimea. Analysis of the data allows to assert that at present the whole territory of Ukraine belongs to the winter range of V. murinus. New winter records of V. murinus from Ukraine and other countries of NE Europe should probably be considered as an evidence of the expansion of the species’ winter range, that may be conditioned by the appearance of big massifs of rock-like structures (= multi-storey buildings) in plain regions. Отсутствие зимних находок и известные дальние перелеты двухцветных кожанов, окольцованных в северо-восточной (СВ) Европе, а также некоторые наблюдения сезонных концентраций мигрирующих животных — всё это позволяло рассматривать до относительно недавнего времени Vespertilio murinus как вид-мигрант, который зимует за пределами Украины и СВ Европы в целом. В течение последних лет вид в Украине отмечен в зимний период (конец октября — середина марта) в 14 областях и АР Крым: контактные регистрации — в 7 областях, регистрация осенней брачной песни — в 9 областях и АР Крым. Имеющиеся данные позволяют утверждать, что территория Украины на сегодня полностью входит в зону зимовки вида. Новые зимние находки V. murinus из Украины и других стран СВ Европы, вероятно, следует рассматривать как доказательство расширения зимовочной зоны вида, которое может быть обусловлено появлением крупных массивов скалообразных структур (= многоэтажные дома) в равнинных регионах.